Case study: BalBukNCo / Siti Noramira Salleh … [et al.] - Salleh, Siti Noramira; Mohd Hattar, Muhammad Luqman Hakim; Baharudin, Muhammad Shaiful Haslim; Rusdi, Nor Syahirah (2022)
BalBukNCo. Resources is an enterprise company with an address at Lorong Chin Kampung Balik Bukit Chuping. It was created at the end of 2019 during the last pandemic period. BalBukNCo refers to Balik Bukit Nature and Community. In accordance with its existence, they apply three important elements in building this business, namely the natural ecosystem, the social ecosystem, and the economic ecosystem. Through these three elements, BalBukNCo is divided into five administrative cores in balancing the business ecosystem, namely BalBuk Haus, BalBuk Dapoq, Kebun BalBuk, Pondok Balbuk and Kampung BalBuk. BalBuk Haus is an independent space for art events and a small cafe in the middle of Bendang with the concept of outdoor, discussion and food. BalBuk Haus has been mapped as an art ecosystem location for the state of Perlis in the Malaysian Art Tour in March 2022 by the National Visual Arts Centre under the Ministry of Arts and Tourism. The goal for this business is to sustain and be profitable for a long time. They have good relationships with customers as they have regular customers each day. They also have a good relationship with customers. Even though it is just a small business, it is still strong till this day as they are still making profit. There are few findings that we found in BalBuk Haus. Firstly, there is no variety of foods in the menu and second is the lack of marketing. The solution provided was to add different choices and menu in the café and boost marketing effort using social media platforms. In conclusion, there is no such perfect business. There will always be room for improvement in every aspect. With larger goals, you may have to establish a more complex measurement process, like increasing profit by a set percentage, or gaining a particular number of new customers. Before you start making changes, it is a good idea to make sure you have a full understanding of the factors affecting your business success, it will help you keep your plan on track and aim for higher objectives.